Tafsir dan Ilmu Tafsir Al-Quran - Mikail Aydin Muhammad; Nur Salamatul Khasanah; Natasya Salsabila; Eva Efiana; Khoirul Aziz; Celvin Pratama Putra; Ananda Putri; Ani Marlia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Qur'an is the greatest miracle of Islam that is eternal and is also a source of knowledge that never conflicts with the progress of human science, but the validity of miracles is increasingly visible. Allah SWT revealed it to the Prophet Muhammad SAW, in order to free humans from the various darknesses of life towards Divine light and guide them to the right path. Rasulullah saw conveyed to his friends that, as native Arabs, he could understand their character. The friends were very eager to receive teachings on the Qur'an from the Prophet Muhammad. They want to memorize the Koran and understand it. Apart from that, the Qur'an has declared itself to be a book of guidance that can guide humans to the right path. Apart from that, He also functions as an explainer of everything and differentiates between truth and falsehood. Various efforts have been made by a number of competent experts and Ulama to reveal clues and explanations to interpret the Al-Qur'an. from the beginning until now. The beauty of the language of the Qur'an, the depth of its meaning, and the diversity of its themes, means that what it contains never diminishes, let alone ends, even though it has been studied from various aspects. Greatness and wonder always emerge with the development of human reason from time to time. Its contents seem to last in the heat and do not rot in the rain. Therefore, efforts to present the messages of the Qur'an are a process that never ends as long as humans are present on earth. From here emerged a number of tafsir works in various styles and methodologies, such as the tafsir of Ibn Abbas, At-Thabari, Ibnu Käsir, Asy Syaukani and others.